Vimbuza The Healing Dance of Northern Malawi - Soko, Boston (Imabali text, 2014)
The purpose of this book is to show that the possession cult of Vimbuza presents itself as an oral genre which is part and parcel of African Oral Literature. The ethno-linguistic study which we undertake will permit us to catch a glimpse of its whole complexity. The analysis has a bearing on four principal aspects. Historical developments: a certain number of facts concerning the birth of possession among the Tumbuka; possession: the study attempts to show how the cult articulates itself with its beliefs and the use of divination; the social role: analysis of social functions; the style: an analysis of the linguistic procedures which are characteristic of Vimbuza songs. The presence of rhetorical figures would confirm that we are talking about an oral literary genre.